DNA testing for fragile X syndrome in schools for learning difficulties. Issue 1 (January 1995) - Slaney, S F; Wilkie, A O; Hirst, M C; Charlton, R; McKinley, M; Pointon, J; Christodoulou, Z; Huson, S M; Davies, K E
Abstract : Fragile X syndrome is the most common inherited cause of mental retardation. Early diagnosis is important not only for appropriate management of individuals but also to identify carriers who are unaware of their high risk of having an affected child. The disorder is associated with a cytogenetically visible fragile site (FRAXA) at Xq27.3, caused by amplification of a (CGG)n repeat sequence within the gene at this locus designated FMR1. Clinical and molecular studies have been undertaken to screen for fragile X syndrome in 154 children with moderate and severe learning difficulties of previously unknown origin. Southern blot analysis of peripheral blood showed the characteristic abnormally large (CGG)n repeat sequence associated with fragile X syndrome in four of the 154 children. The findings were confirmed by cytogenetic observation of the fragile site and by further molecular studies. The families of the affected children were offered genetic counselling and DNA tests to determine their carrier status. These findings show that there are still unrecognised cases of fragile X syndrome. Given the difficulty of making a clinical diagnosis and the implications for families when the diagnosis is missed, screening in high risk populations may be justified. The issues involved in screening all children in special schools for fragile X syndrome are discussed.